2013
DOI: 10.5430/jms.v4n2p60
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Human Resource Management Practices and Entrepreneur Training on Innovation and Small-Medium Firm Performance

Abstract: A large number of studies on innovation can be found in the literature, yet until recently, research on the moderating effects of HRM practices and entrepreneur training on the relationship between innovation and firm performance are nonexistent. This study attempts to address the questions of how HRM practices and entrepreneur training interact with innovation, which then affect SMF performance. Two hundred eighty-four samples were obtained from SMFs in Malaysia. This study found that the employee and employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 46 publications
3
19
1
Order By: Relevance
“…Results of the PLS path modeling indicated significant positive relationship between entrepreneurial training and organizational performance. Whilst addressing the research limitations (Rosli & Mahmood, 2013), the present study has forwarded results consonance with previous study (Morris & Jones, 1999), suggesting that entrepreneurial training can help employees gain skills that enable them to bring innovativeness, creativity and versatility in their work which hence results in enabling the business to boost its overall performance. In this, the study has outlined that employees working in top positions in the public-sector universities were provided with valuable entrepreneurial training prospects.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Results of the PLS path modeling indicated significant positive relationship between entrepreneurial training and organizational performance. Whilst addressing the research limitations (Rosli & Mahmood, 2013), the present study has forwarded results consonance with previous study (Morris & Jones, 1999), suggesting that entrepreneurial training can help employees gain skills that enable them to bring innovativeness, creativity and versatility in their work which hence results in enabling the business to boost its overall performance. In this, the study has outlined that employees working in top positions in the public-sector universities were provided with valuable entrepreneurial training prospects.…”
Section: Discussionsupporting
confidence: 80%
“…To examine entrepreneurial culture, three-item scale by Yeung et al (1991) was adapted. Accordingly, Rosli and Mahmood's (2013) two item scale was used to assess entrepreneurial training and four item scale to examine organizational performance by Covin and Slevin (1989). Lastly, the moderation of government funding was tested through ten-item scale by Lai (1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, hypotheses 1 is supported. These support the findings of the previous studies (Barbero et al, 2011;Jayawarna et al, 2014;Garavan et al, 2015;Rosli & Mahmood 2013) that linked educational qualification and skills to different organizational performance indices and contradicts the Kfindings of Rauch, Frese, and Utsch (2005) …”
Section: Human Resourcesupporting
confidence: 83%
“…Human resources: Data were gathered on knowledge (measured by relevant educational level and experience) and skills (measured by cognate abilities and special skills). Past research on the relevance of human resources to the performance of SMEs revealed a positive relationship (Bharadwaj & Menon, 2000;Hambrick & Mason, 1984;Muller & Gangl, 2003;Piva & Vivarelli, 2009;Rosli & Mahmood, 2013). Storey's (2004) study found that it is the first major resource in competition and it plays the decisive role in the allocation and use of resources for enterprise production and business operation that guarantee growth.…”
Section: Theoretical Frameworkmentioning
confidence: 97%